Validitas dan Praktikalitas Komik Digital terintegrasi Etnosains pada Materi Termokimia untuk Meningkatkan Literasi Kimia Peserta Didik - Adib Asyrof; Andromeda (MASALIQ, 2026)
Chemical literacy is an essential competency that students need to possess to address global challenges and develop critical thinking and science-based problem-solving skills. However, chemical literacy among secondary school students remains relatively low, partly because chemistry instruction is still dominated by monotonous and insufficiently varied conventional media, thereby limiting students’ learning interest and active engagement. This study aims to produce an ethnoscience-integrated digital comic on thermochemistry for Phase F SMA/MA that meets the criteria of validity and practicality. This study employed the Research and Development method using a modified Plomp development model comprising three stages: preliminary research, development and prototyping phase, and assessment phase. The findings show that the ethnoscience-integrated digital comic obtained an average Aiken’s V value of 0.82 and was classified as valid. The practicality tests conducted by teachers and students yielded average percentages of 90% and 85.28%, respectively, both of which were classified as highly practical. This study concludes that the ethnoscience-integrated digital comic on thermochemistry has adequate levels of validity and practicality and is therefore suitable for use as a chemistry learning medium for Phase F SMA/MA. These findings contribute to the development of contextual and innovative chemistry learning media and support the strengthening of chemical literacy through the integration of scientific knowledge and local wisdom.